Utilization of The Thrasher and Rice Mill Machines in Composition Function Learning: A Hypothetical Learning Trajectory Design - Ulfa Masamah; Dadan Sumardani (Program Studi Tadris Matematika IAIN Salatiga, 2021)
The study aims to design mathematics learning in composite function concepts with farm tools, which are thrasher and rice mill machines; this farm’s tool is used as to starting point in the learning process. The research method used is design research with a preliminary design, design experiment, and analysis retrospective stages. This study describes the design of the thrasher and rice mill machine to facilitate a real contribution for student understanding of the composite function concept. The participant of this research is 10 eleventh-grade students from one of the senior high school in East Java. The results of this study reveal that students are able to make associations from the thrasher and rice mill machine through the determination of the input and output of the machines to the formula of the composite function concept. So, the stages in the learning trajectory have an important role in understanding the composition function concept from informal level to formal level and also make the study of mathematics more easy, simple, fun, and comfortable.